APLIKASI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN PRODUKSI PADI DI LAHAN SAWAH - Eli Korlina; Diding Rachmawati; Sri Zunaini Saadah (Bioplantae, 2013)
This study aims to determine the optimal dose effect of the use of biofertilizers on growth and rice production in the field. The study was conducted from October 2013 to February 2014, in Kepung district, Kediri. The design used was a randomized block design (RBD) was repeated 3 times, with treatment as much as 13, which is a combination of biofertilizer (0, 30, 60, 90 kg/ ha), organic matter (0, 1000, 2000, 3000 kg/ha) and fertilizer (NPK 60%: 50%: 100%). For comparison (farmers) are no biofertilizer, of 300 kg urea+48 kg SP 36+50 kg KCl/ha. The results showed that the biofertilizer application had no significant effect on plant height, but the real impact on the number of tillers. The combination of biofertilizer 30 kg/ha and organic materials 3 tons/ha gives the highest number of tillers, with weights GKP production of 7.04 t/ha. While the production of GKP highest weight (7.38 t/ha), resulting in a biolfertilizer dose combination treatment of 60 kg/ ha+organic material 3 t/ha, followed by treatment of the combination of biofertilizer dose of 90 kg/ha+organic material 3 t/ha of 6.9 t/ha, as well as a combination of biofertilizer dose of 90 kg / ha+organic material 1 t/ha of 7.05 t/ha. Pest appears that rice stem borer and blast disease with relatively low attack. Keywords: rice, biofertilizer, the optimal dose, growth, yields